Including culture in programs to reduce stigma toward people with mental disorders in low- and middle-income countries. (February 2020) - Mascayano, Franco; Toso-Salman, Josefina; Ho, Yu Chak Sunny; Dev, Saloni; Tapia, Thamara; Thornicroft, Graham; Cabassa, Leopoldo J; Khenti, Akwatu; Sapag, Jaime; Bobbili, Sireesha J; Alvarado, Rubén; Yang, Lawrence Hsin; et al.
Stigma is one of the main barriers for the full implementation of mental health services in low- and middle-income countries (LMICs). Recently, many initiatives to reduce stigma have been launched in these settings. Nevertheless, the extent to which these interventions are effective and culturally sensitive remains largely unknown. The present review addresses these two issues by conducting a comprehensive evaluation of interventions to reduce stigma toward mental illness that have been implemented in LMICs. We conducted a scoping review of scientific papers in the following databases: PubMed, Google Scholar, EBSCO, OVID, Embase, and SciELO. Keywords in English, Spanish, and Portuguese were included. Articles published from January 1990 to December 2017 were incorporated into this article. Overall, the studies were of low-to-medium methodological quality—most only included evaluations after intervention or short follow-up periods (1–3 months). The majority of programs focused on improving knowledge and attitudes through the education of healthcare professionals, community members, or consumers. Only 20% (5/25) of the interventions considered cultural values, meanings, and practices. This gap is discussed in the light of evidence from cultural studies conducted in both low and high income countries. Considering the methodological shortcomings and the absence of cultural adaptation, future efforts should consider better research designs, with longer follow-up periods, and more suitable strategies to incorporate relevant cultural features of each community.